2015
DOI: 10.1126/science.aaa2491
|View full text |Cite
|
Sign up to set email alerts
|

Technology-driven layer-by-layer assembly of nanofilms

Abstract: Multilayer thin films have garnered intense scientific interest due to their potential application in diverse fields such as catalysis, optics, energy, membranes, and biomedicine. Here we review the current technologies for multilayer thin-film deposition using layer-by-layer assembly, and we discuss the different properties and applications arising from the technologies. We highlight five distinct routes of assembly—immersive, spin, spray, electromagnetic, and fluidic assembly—each of which offers material an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
1,000
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,396 publications
(1,023 citation statements)
references
References 101 publications
(231 reference statements)
7
1,000
0
16
Order By: Relevance
“…4 The development of fast, inexpensive, and up-scalable fabrication methods for stratified systems is a key challenge in materials science. 5,6 Here, we introduce a method to obtain self-assembled stratified coatings, along with a simple means to form homogeneous coatings, when desired, using the same starting materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 The development of fast, inexpensive, and up-scalable fabrication methods for stratified systems is a key challenge in materials science. 5,6 Here, we introduce a method to obtain self-assembled stratified coatings, along with a simple means to form homogeneous coatings, when desired, using the same starting materials.…”
mentioning
confidence: 99%
“…19 A means to adjust stratification without altering the starting composition or the deposition method would offer a huge efficiency gain over conventional fabrication technology. 6,[20][21][22] Our vision in the design of a switchable, stratified coating is to draw upon insights from our earlier work 23 to bring together two different materials technologies: colloidal stratification and pH-responsive particles. Here, we show how the stratification of binary particle blends can be switched off (or on) simply by raising (or lowering) the pH of the initial dispersion.…”
mentioning
confidence: 99%
“…Regarding the coating strategy, the layer-by-layer assembly protocol of immersing seeds into solutions of desired materials has been a successful practice for anchoring different species. 29 However, such an immersion process is also well known for its shortcomings; the process is time consuming and it must be carefully operated to produce a satisfactory coating. Kim et al 18 reported a synthetic strategy to construct the core-shell structure of MWCNTs@FePO 4 , which required the alternate immersion of the substrate material into an Fe 3+ solution and a H 2 PO 4 − solution several times.…”
Section: Introductionmentioning
confidence: 99%
“…Another new element in our approach, compared to the previous numerical and experimental studies of the patchy particles, is the use of layer-by-layer growth protocol. This is a well known technique in material science and chemical engineering [23][24][25], and as we show below, it can be employed in the context of patchy particles to create periodic structures of exceptional quality.…”
Section: Introductionmentioning
confidence: 99%